Analisis Perilaku Proaktif Pegawai pada Instansi X - Asyifa Rahmatia; Christian Wiradendi Wolor (CV Muara Edukasi, 2026)
Proactive behavior is an important work behavior in supporting organizational effectiveness, particularly in dynamic work environments. This study aims to examine the forms of proactive behavior demonstrated by employees, the conditions associated with its emergence, and the organizational context that supports the development of such behavior at Institution X. The study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving four informants selected using purposive sampling, and were subsequently analyzed using an interactive analysis model. The findings indicate that proactive behavior is manifested through initiatives in carrying out work, improving work processes, utilizing technology, and actively supporting organizational needs. The emergence of such behavior is associated with job demands, service requirements, and individuals’ ability to adapt. In addition, leadership support, open communication, positive workplace relationships, and the availability of adequate work facilities contribute to the development of proactive behavior. The findings show that proactive behavior develops through the interaction between individual factors and a supportive organizational environment.